2019
DOI: 10.1088/1742-6596/1363/1/012094
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove diversity and sustainability in karangsong village of indramayu regency, west java

Abstract: Mangrove forests in the northern coastal region of Karangsong Village, Indramayu Regency, West Java, form a crucial component of the livelihoods of coastal communities. The objective of this research is to know the diversity of species and mangrove vegetation based on growth level. The research method is explorative survey technique method. The data collection for the research vegetation data from 10 plots divided from observed tracks. This study resulted in the observation 9 species of plants: Avicennia marin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Based on the data above, even though the substrate is sandy and slightly rocky, the Rhizophora type is a type of mangrove that is almost always found in every plant category, both in the Tree, Sapling, and Seedling categories. This is due to the ability of Rhizophora mangroves to live in various substrate conditions [11], unlike other types of mangroves.…”
Section: Bagik Batu Mangrove Community Structurementioning
confidence: 99%
“…Based on the data above, even though the substrate is sandy and slightly rocky, the Rhizophora type is a type of mangrove that is almost always found in every plant category, both in the Tree, Sapling, and Seedling categories. This is due to the ability of Rhizophora mangroves to live in various substrate conditions [11], unlike other types of mangroves.…”
Section: Bagik Batu Mangrove Community Structurementioning
confidence: 99%
“…Gunawan [7] stated that 12 bird families consisting of 20 species were found in mangroves and coastal vegetation in Karangsong, while Sihombing et al [15] reported 14. Based on Majesty et al [17], observations there are 9 plant species, namely Avicennia marina, Avicennia alba, Casuarina equisetifolia, Rhizophora apiculata, Rhizophora stylosa, Rhizophora mucronata, Terminalia catappa, Thespesia populnea, and Ziziphus mauritiana. From the analysis, it is known that the dominant species in Karangsong is Rhizophora mucronate.…”
Section: Karangsong's Mangrove Resourcementioning
confidence: 99%